ADDITIONAL EMPLOYEE BENEFITS: FEATURES OF ACCOUNTING AND TAXATION (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article deals with problems related to the accounting interpretation of the additional benefits of the employee, which should be evaluated and identified in accounting as a separate object. However, benefits are specific in their manifestations, which causes certain difficulties in recognition and taxation. Tangible or intangible values, services, other types of income paid to the employee (tax payer) by the employer (tax agent) are additional benefits. Their main criteria are that the income is not the employee's salary; is not a reward under a civil law contract; not related to the performance of employment obligations. Deepening the nature of the subject of accounting in modern conditions, its constant improvement involves the appearance of new objects that do not limit it, but add details to the content of its theories. Caring for the health and life of employees is one of the main social policy priorities of not only foreign enterprises, but also domestic ones. Thus, in addition to material reward in the form of wages or social guarantees, the employee may be offered a generous social package. The issue of understanding the concept of "benefit" is extremely important not only for a purely theoretical understanding of the object of civil legal relations, but also for the practical delimitation and definition of objects received by the subject of civil or labor legal relations as such, which are beneficial (additional benefits), and those that are not beneficial. Additional benefits are funds, tangible or intangible values, services, other types of income paid (provided) to a taxpayer by a tax agent, if such income is not a salary and is not related to the performance of employment obligations or is not a reward according to civil law contracts (agreements) concluded with such a taxpayer.
Keywords: Additional benefits, wages, personal income tax, accounting, taxation, military tax, object of accounting, taxes.